Natural ventilation impact on selected IEQ parameters and users’ satisfaction in central spaces of shopping malls in Malaysia - Idowu, Ibiyeye Aminat (2017)
In order to consistently meet the demand for quality indoor environment, as well as gaining high users’ satisfaction and attaining efficient energy usage, new trends have been developing in the design of Malaysian shopping malls. From fully air-conditioned models to newly designed ones that integrate passive ventilation strategies, and as such these shopping malls are operating under mixed-mode ventilation system. These passive ventilation strategies are implemented in order to improve the indoor environment and also to reduce energy consumption. However, the potential of these designs in terms of their indoor environmental quality (IEQ) performance and users’ satisfaction with the malls’ performance has not been studied. This research investigated the IEQ performance and users’ satisfaction of two mixed-mode ventilated malls and one fully air-conditioned mall. The study was conducted in two phases: 1) Identification and classification of mixed-mode ventilated malls in Malaysia, and 2) building performance. The first phase was carried out in order to identify mixed-mode ventilated malls currently under operation in Malaysia and the results of this study were used as the basis for selecting the mixed-mode ventilated case study malls. The two mixed-mode ventilated malls were selected based on their design concepts (‘enclosed’ and ‘hybrid’). For the IEQ performance, five measured environmental factors (air temperature, operative temperature, relative humidity, air speed, and CO2) and five satisfaction factors (thermal, indoor air quality, air movement, workplace/present location, and overall building performance satisfaction) were evaluated in all case study malls using field measurements and questionnaire survey. Field measurements were done only within the naturally ventilated central spaces in the mixed-mode ventilated malls and only users within these spaces were surveyed. The results from the IEQ performance revealed that all three case study malls performed differently. Generally, the ‘hybrid’ concept mixed-mode ventilated mall proved to be superior to the ‘enclosed’ concept one and it was similar in performance to the air-conditioned mall in terms of users’ satisfaction except in the case of its overall performance satisfaction where its performance was better. Although all three case study malls failed to comply with the ASHRAE standard 55 for thermal comfort in an occupied space, yet thermal acceptance was high in all case study malls. The users within the naturally ventilated spaces of the ‘hybrid’ concept mixed-mode ventilated mall showed higher thermal tolerance and air movement was found to be of utmost importance to workers in the two mixed-mode ventilated malls. Findings from this study were able to prove that natural ventilation could be enhanced and use in malls to improve the IEQ performance and at the same time achieve high users’ satisfaction. The results can potentially be used to help designers in creating malls that are more efficient in resourcesand also safer and healthier for users and the environment.